2003
DOI: 10.1076/phbi.41.2.107.14240
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Compounds Isolated From Plants

Abstract: This review presents 344 compounds isolated and identified from plants that previously demostrated antiviral activity. These compounds have been classified in appropiate chemical groups and data are reported on their pharmacological effect, mechanism of action, and other properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 106 publications
(114 reference statements)
0
53
0
2
Order By: Relevance
“…Phenolic compound have antimicrobial (Taguri et al 2006), antimutagenic, (Lairon and Amiot 1999), antiviral (Perez 2003), anticarcinogenic (Aaby et al 2004), anti-inflammatory (Dos Santos et al 2006), antiproliferative and vasodilatory actions (Lule and Xia 2005) and have potential preventive properties against cardiovascular diseases, hormonal related cancers (Gupta and Abu-Ghannam 2012). In addition, to their antioxidant properties, isoflavones and lignans exert a weak oestrogenic activity (Barnes et al 2000), which may be implicated in several mechanisms protecting the human body and also have been suggested to reduce the risks of cancer and to lower serum cholesterol (Barnes et al 2000).…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Phenolic compound have antimicrobial (Taguri et al 2006), antimutagenic, (Lairon and Amiot 1999), antiviral (Perez 2003), anticarcinogenic (Aaby et al 2004), anti-inflammatory (Dos Santos et al 2006), antiproliferative and vasodilatory actions (Lule and Xia 2005) and have potential preventive properties against cardiovascular diseases, hormonal related cancers (Gupta and Abu-Ghannam 2012). In addition, to their antioxidant properties, isoflavones and lignans exert a weak oestrogenic activity (Barnes et al 2000), which may be implicated in several mechanisms protecting the human body and also have been suggested to reduce the risks of cancer and to lower serum cholesterol (Barnes et al 2000).…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…The result of the enzyme inhibition assay showed that all seven standard compounds exhibited anti-influenza virus activity, and pentagalloylglucose, benzoylpaeoniflorin, albiflorin and paeoniflorin showed stronger activity against NA than Oseltamivir acid. In several literature reports [28][29][30], the antiviral activities of pentagalloylglucose and gallic acid have been reported, but there are few reports regarding the antiviral activities of methyl gallate, ethyl gallate, benzoylpaeoniflorin, albiflorin and paeoniflorin. In this study, the NA inhibitory activity of methyl gallate, ethyl gallate, benzoylpaeoniflorin, albiflorin and paeoniflorin were reported for the first time.…”
Section: Chemicals and Standard Substancesmentioning
confidence: 99%
“…Baillon is a deciduous, woody stem liana from the Schisandraceae family, which belongs to primitive dicotyledon plants with undifferentiated embryos. This compounds display significant antioxidant action and some of them were identified as potent anti-human immunodeficiency virus agent (Perez 2003). Schisandra chinensis contains dibenzo- [a,c]cyclooctadiene lignans that are unique natural substances.…”
mentioning
confidence: 99%